PENGEMBANGAN MEDIA ULAR TANGGA DENGAN MODEL REALISTIC MATHEMATICS EDUCATION PADA PEMAHAMAN KONSEP MATEMATIKA - Akhidah , Dewanti Nur; Zuliana, Eka; Ermawati , Diana (Universitas Insan Budi Utomo, 2023)
Monotonous and conventional learning using the lecture method can cause students to be less interested in learning. This causes the concept given not to imprint sharply in the memory of students so that students easily forget and often confused in solving a problem that is different from what is exemplified by the teacher. The purpose of this study is for the feasibility, effectiveness, and development of snakes and ladders media with a Realistic Mathematics Education model on understanding mathematical concepts. In this study, research and development (R&D) research methods were used. This research will be carried out in grade IV SDN Tambirejo with research subjects of 10 students and teachers. The subject selection of 10 students was obtained from the postest and prettest assessments. For teachers, an assessment was obtained from the results of interviews between researchers and teachers. The dependent variable in this study is understanding the concept, while the independent variable is a Realistic Mathematics Education model assisted by two snakes and ladders. Data collection techniques include interviews, observations, tests, and documentation. The data analysis used is qualitative and quantitative data analysis. The results of this study show that Snakes and Ladders media is very feasible to use, shown by the percentage of media feasibility of 77% and material feasibility of 88%. The N-Gain test showed a result of 0.1785 with the